(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The number of children with dyslexia is estimated to be continuously increased in Malaysia. Dyslexia affects the academic learning capacity of children, thus affecting the academic achievement as well. Issues related to dyslexia have led to a more complex role and experience of mothers in taking care of their children with dyslexia as compared to mothers with normal children. This study employed Interpretative Phenomenological Analysis (IPA) to explore the experiences of the mothers involved which included the challenges faced, and coping skills and their hopes in raising children with dyslexia. As a result, three themes have emerged: â€œlifeâ€˜s bitternessâ€œ that was related to the lack of time, living expenses, negative feelings, educational issues and distressful role as a mother; â€œNever mind, I take it that wayâ€¦â€ that was related to the extra effort; and â€œI wishâ€¦â€ that was related to a need for improvement. In conclusion, mothers should be equipped with multi-disciplinary skills such as occupational therapy and psychology, besides other related skills as the key to help children with dyslexia. Health professionals also need to have a better understanding of raising children with dyslexia so that a more effective role in addressing this learning disability can be provided.Â